Beyond the building: Unleashing leadership potential in the graduate classroom - Perkins, Miriam Yvonne (Teaching theology and religion, 2021)
This essay explores how classroom teaching and learning can become an incubator for leadership skills graduate students need to enhance community well-being. Teaching leadership skills at the graduate level, however, is often siloed into an elective course or internship. The developing field of humanitarian architecture addresses the need for leadership skills by prioritizing design thinking oriented toward collaborative community transformation. In conversation with humanitarian architecture's themes, this essay offers three classroom case studies exploring compelling ways to nurture leadership skills in the graduate theological classroom and beyond: (1) disrupt power differentials by sharing leadership with students; (2) create or retool a single course assignment to develop and assess a needed leadership competency; and (3) explore learning beyond the building by working in partnership with community leaders and organizations. Humanitarian architecture's focus on “building for community transformation” provides theological educators a guiding metaphor for teaching the public pastoral leadership skills faith communities need to navigate the future.